Comparative Evaluation of Microscopy and Loop-Mediated Isothermal Amplification (Lamp) Assay for the Diagnosis of Tuberculosis - Ni Njoman Juliasih, Rajesh Kumar Das2 , Ni Made Mertaniasih3 , Prabin Neupane4, , Reny Mareta Sari5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tuberculosis (TB) is one of the major global health problem which affects millions of people each year. For the routine diagnosis of TB, microscopic technique is used but it has lower sensitivity and specificity. This study was carried out to evaluate the efficacy of loop mediated isothermal amplification (LAMP) over smear microscopy to detect Mycobacterium tuberculosis. Out of 84 processed samples processed in this study, the diagnostic tests showed varying results. Using smear microscopy, 16(19.05%) and with the LAMP assay, 17(20.24%) cases were found positive for M. tuberculosis. The sensitivity of the LAMP assay (87.5%) was greater than that of microscopy (82.35%) while the specificity of both methods was comparable (>95%). Being more sensitive than microscopy, LAMP assay is more likely to show the positive result and solve the errors in diagnosis of the TB cases. Thus, LAMP assay can be an important and cost-effective tool for appropriate and timely diagnosis of TB patients. This can further assist to implement intervention programs against TB.